The effects of laughter programs on nursing students’ laughter index, self-esteem, and career decision making self-efficacy - Lee, Hyunjung (Edelweiss Applied Science and Technology, 2024)
The purpose of this study was to conduct a laughter program for third-year nursing students who completed the first semester of hospital practice, to investigate the effects of the laughter program on nursing students’ laughter index, self-esteem, and career decision making self-efficacy, and to identify the relationship between laughter index, self-esteem, and career decision making self-efficacy. Data from a total of 29 subjects who experienced the laughter program (intervention time: 2 sessions for 60 minutes, number of applications: once a week, a total of 6 times over 3 weeks) were analyzed (paired t-test, Pearson correlation coefficient). Laughter programs were confirmed to have a significant impact on laughter index, self-esteem, and career decision making self-efficacy, and laughter index had a statistically significant positive correlation with career decision making self-efficacy. Therefore, if the laughter program is utilized, the positive self-management can be induced by increasing interest and motivation for studying and employment, and it can guide the students to resolve negative emotions such as psychological tension caused by excessive study load, stress due to hospital practice, and burden of employment.